Transformasi Digital Pelayanan Publik: Studi Kasus Aplikasi ASSiK di Kota Surabaya - Sembiring, Amelia L Pepayosa; Ananta Prathama (Sawala : Jurnal Administrasi Negara, 2025)
Government services must be able to innovate in the era of globalization, especially in terms of providing better services to meet people’s needs and solve problem with current technology. The Surabaya City Government is also carrying out regional innovations to provide digital-based public services namely through the ASSiK (Arek Suroboyo Siap Kerjo) application. ASSiK is digital platform designed to bring together job seekers with companies that need workers in order to disseminate job vacancy information so as to increase labor absorption in the City of Surabaya. This research aims to describe the innovation of the ASSiK application in increasing the efficiency of public services, user satisfaction and employment in teh City of Surabaya. Using a qualitative approach, this research collected data through interviews and document analysis. The research results show that ASSiK has made a positive contribution in speeding up the job search process, increasing the transparency of vacancy information and expanding access for job seekers. However, there are still several challenges that need to be overcome, such as improvements and development in the performance of the application’s functions and features. Thus, this application can be more comfortable for users to use.